The Need to Deepen the Abscopal Effect and Synergy among Radiotherapy and Immunotherapy - Denaro Nerina (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2018)
Emerging data that radiotherapy can potentially convert the patient's own tumor into an in situ vaccine have raised significant interest for testing radiation in combination with immunotherapy. Moreover, the immune responses to localized irradiation may be the mediator of systemic effects (called the abscopal effect).